2022
DOI: 10.1002/essoar.10512246.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semi-automatic tuning of coupled climate models with multiple intrinsic timescales: lessons learned from the Lorenz96 model

Abstract: The History Matching method is explained in detail then used for tuning a toy coupled model: the Lorenz 96 model • The importance of several design choices is demonstrated, especially when considering forced experiments such as AMIP and OMIP • We argue that this tuning method is semi-automatic and highlight the importance of the expert-in-the-loop paradigm when considering it for real coupled models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Where σ z is the observational uncertainty and σfˆ ${\sigma }_{\widehat{f}}$ is the uncertainty in the emulator prediction. Typically for the univariate case (Andrianakis et al., 2015; Couvreux et al., 2021; Lguensat et al., 2023; Williamson et al., 2013), Pukelsheim's rule is invoked which states that for a continuous unimodal distribution 95% of the probability mass lies within 3 standard deviations of the mean value (Pukelsheim, 1994). For the multivariate case, as in this work with a 2‐dimensional z , there are various definitions of the implausibility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where σ z is the observational uncertainty and σfˆ ${\sigma }_{\widehat{f}}$ is the uncertainty in the emulator prediction. Typically for the univariate case (Andrianakis et al., 2015; Couvreux et al., 2021; Lguensat et al., 2023; Williamson et al., 2013), Pukelsheim's rule is invoked which states that for a continuous unimodal distribution 95% of the probability mass lies within 3 standard deviations of the mean value (Pukelsheim, 1994). For the multivariate case, as in this work with a 2‐dimensional z , there are various definitions of the implausibility.…”
Section: Methodsmentioning
confidence: 99%
“…This approach was initially developed to calibrate models for oil exploration (Craig et al., 1997) and has found wide utility in various disciplines. This includes in calibrating models of galactic formation (Williamson et al., 2013), HIV disease transmission (Andrianakis et al., 2015) and recently in calibrating multi timescale dynamical systems (Lguensat et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Where σ z is the observational uncertainty and σ f is the uncertainty in the emulator prediction. Typically for the univariate case (Andrianakis et al, 2015;Lguensat et al, 2023;Couvreux et al, 2021;Williamson et al, 2013), Pulksheim's rule is invoked which states that for a continuous unimodal distribution 95% of the probability mass lies within 3 standard deviations of the mean value (Pukelsheim, 1994). For the multivariate case, as in this work with a 2-dimensional z there are various definitions of the implausibility.…”
Section: History Matchingmentioning
confidence: 99%
“…This approach was initially developed to calibrate models for oil exploration (Craig et al, 1997) and has found wide utility in various disciplines. This includes in calibrating models of galactic formation (Williamson et al, 2013), HIV disease transmission (Andrianakis et al, 2015) and recently in calibrating multi timescale dynamical systems (Lguensat et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation